(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2020)
Memory making in schools evidences complex elaborations produced by their agents, as well as an equally heavy link with the contexts in which it is developed. Grasping this complexity is a challenge for those who study this subject. Through the analysis of compositionswritten by two groups of students in a public and a private high school from the city center of La Plata, I propose a survey on the mediations between youth people and recent past, and on their social representations. The definition of categories and the qualitative as well as quantitative study of their links in the interpretative and justifying dimensions show us,on the one hand, the persistence of school culture and a nationalistic and formally liberal frame of reference. On the other hand, identifications, appropriations, certain political attitudes and inventiveties with social memories are witnessed. Finally, a contrast between public and private schools is also attested.Thus, I explore memory making on the grounds in which it is elaborated and not only in relation to the values researchers have for the sake of democratization, which in turn constitute a necessary but not a sufficient condition.